INVESTIGATING ABILITY IN WRITING DESCRIPTIVE TEXT OF GRADE VIII STUDENTS AT SMP NEGERI 18 SIGI - Sagita, Evi; Mukrim, Mukrim; Maf'ulah, Maf’ulah; Jamiluddin, Jamiluddin (Tadulako University, 2024)
This research aims to find out whether the application of descriptive text is effective in improving the writing skills of grade 8 (eight) students at SMP Negeri 18 Sigi. This research uses descriptive qualitative methods. This population is students in class 8 (eight) of Sigi State Middle School, consisting of 100 people. Sample selection was carried out in total. The test was used to collect data consisting of a pre-test and post-test. The test results showed that the average pre-test score obtained was 59.58. After carrying out the post test the results showed that there were 85% of students who were competent and 15% who were not competent. Increasing students' abilities means that the application of descriptive text to grade 8 (eight) students at SMP Negeri 18 Sigi was declared successful.